Agonistic behaviour of breeding Pink-footed Geese with reference to Ryder’s hypotheses - Inglis, I R (Wildfowl, 1976)
The recent proposals of Ryder (1975) are examined in the light of behavioural studies conducted in Iceland on the Pink-footed Goose Anser brachyrhynchus. It is concluded that the main function of agonistic behaviour in this species is to safeguard a supply of food, primarily for the female, at the beginning of the nesting period. Ryder’s suggestion that the function of the territory is to protect the incubating female from harrassing conspecifics would seem to be inappropriate.